Do follicles matter? Testing the effect of follicles on hair cortisol levels - Sergiel, Agnieszka; Cattet, Marc; Kapronczai, Luciene; Janz, David M; Selva, Nuria; Bartoń, Kamil A; Swenson, John E; Zedrosser, Andreas (Conservation Physiology, 2020)
Cortisol concentrations in hair are used increasingly as a biomarker of long-term stress in free-ranging wildlife. Cortisol isbelieved to be integrated into hair primarily during its active growth phase, typically occurring over weeks to months orlonger periods, depending on latitude. Cortisol concentrations in hair thus reflect the activity of the hypothalamic–pituitary–adrenal axis over this time. However, local, independent cortisol secretion within the skin, which includes hair follicles, mayalso contribute to cortisol levels in growing hair. Methodological differences between studies include the measurement ofcortisol in only the hair shaft (i.e. follicle absent, as with shaved hair) versus the whole hair (i.e. follicle present, as with pluckedhair). If the concentration of cortisol in the follicle is high enough to influence the overall hair cortisol concentration (HCC), thiscould confound comparisons between studies using different types of hair samples (hair shafts vs. whole hair) and collectionmethods. Here, we test the hypothesis that cortisol present in follicles influences HCC.We compared HCC in paired subsamplesof hair with and without follicles from 30 free-ranging Scandinavian brown bears (Ursus arctos) and observed significantlygreater HCC in samples with follicles present. The effect of follicles remained significant also with sex and age of sampledbears taken into account in a linear mixed model. Finally, we provide an overview of collection methods and types of hairsamples used for HCC analysis in 77 studies dealing with stress in wild mammal species.Our findings highlight the need to unifymethods of hair collection and preparation to allow for valid comparisons, and to optimize labour input in ecophysiologicalstudies. The study was supported by the Polish-Norwegian Research Program, operated by the National Center for Research and Development in Poland under the Norwegian Financial Mechanism 2009–2014 in the frame of Project Contract No. POL-NOR/198352/85/2013 (GLOBE), and has also received ...